2018
DOI: 10.1002/lary.27398
|View full text |Cite
|
Sign up to set email alerts
|

One‐Year symptom outcomes after sialolithiasis treatment with sialendoscopy‐assisted salivary duct surgery

Abstract: 4. Laryngoscope, 2018.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 26 publications
0
9
0
Order By: Relevance
“…Following the further development of minimally invasive techniques such as transoral duct surgery (TDS) [ 3 , 4 , 5 ] and the introduction of new minimally invasive techniques such as extracorporeal shock-wave lithotripsy (ESWL) [ 6 , 7 , 8 , 9 , 10 ] and interventional sialendoscopy (intSE) [ 11 , 12 , 13 , 14 ] between the 1990s and the first decade of the 2000s, the gland resection rate has been substantially reduced—to less than 10% or even less than 5% [ 15 , 16 ]. In particular, sialendoscopy-assisted techniques have been reported to contribute to a reduction in symptoms [ 17 ]. ESWL was then partly replaced by the introduction of combined approaches, particularly for parotid stones [ 18 , 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…Following the further development of minimally invasive techniques such as transoral duct surgery (TDS) [ 3 , 4 , 5 ] and the introduction of new minimally invasive techniques such as extracorporeal shock-wave lithotripsy (ESWL) [ 6 , 7 , 8 , 9 , 10 ] and interventional sialendoscopy (intSE) [ 11 , 12 , 13 , 14 ] between the 1990s and the first decade of the 2000s, the gland resection rate has been substantially reduced—to less than 10% or even less than 5% [ 15 , 16 ]. In particular, sialendoscopy-assisted techniques have been reported to contribute to a reduction in symptoms [ 17 ]. ESWL was then partly replaced by the introduction of combined approaches, particularly for parotid stones [ 18 , 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…They found in patients with sialolithiasis, nonreachable parenchymal sialoliths, and concurrent inflammatory disease and/or stenosis may be the potential risk factors for symptom persistence. 15 Moreover, in patients with chronic obstructive sialadenitis without sialolithiasis, autoimmune sialadenitis, and glands with proximal or multifocal stenoses present with the highest proportion of persistent or recurrent disease. 16 The result from these studies implies that the location of the stone, size of the stone, and the presence of stenosis seem to be essential factors predicting outcomes for intraductal laser lithotripsy.…”
Section: Discussionmentioning
confidence: 99%
“…Sialendoscopy is a low-risk 4 Some studies showed that symptoms after sialendoscopy were improved in short-, medium-and long-term 6 follow-up. [7][8][9][10][11][12][13] In most cases custom designed questionnaires relying on symptom improvement were utilized. Aubin-Pouliot et al 12 used the "chronic obstructive sialadenitis symptoms questionnaire" (COSS) and observed symptom improvement at 3 and 12 months postoperatively.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies showed that symptoms after sialendoscopy were improved in short‐, medium‐ and long‐term 6 follow‐up 7‐13 . In most cases custom designed questionnaires relying on symptom improvement were utilized.…”
Section: Discussionmentioning
confidence: 99%